Penguatan Keterampilan Warga Lembaga Pemasyarakatan Perempuan Kelas II B Padang melalui Edukasi Potensi Ekonomi Budidaya Lebah - Henny Herwina; Jasmi Jasmi; Pebriana Pebriana; Sonia Farmila Syahril; Puti Khairunnajwa Amar; Hylda Hylda (Warta Pengabdian Andalas, 2022)
Stingless bee cultivation in Indonesia is now starting to develop, one of which is in West Sumatra, which has the potential as an effort to improve the community's economy. Stingless bees can produce nutritious products for health, such as honey and propolis, which can be processed into food, drinks, and other products sold at high prices. Community service activities were carried out to help the Class IIB Correctional Institution Padang community increase knowledge about Galo-galo beekeeping. The method used in this activity was helping through socialization, education, and discussion regarding the potential and methods of cultivating Galo-galo honey bees in residential areas and providing business motivation to improve the community's economy. All activities ran smoothly, and they were greeted enthusiastically by the inmates.